PENINGKATAN HASIL BELAJAR OPERASI HITUNG MENGGUNAKAN MEDIA CONGKLAK MODIFIKASI KELAS III DI SEKOLAH DASAR INKLUSI SURABAYA - PURWANINGSIH, DWI; MAHMUDAH, SITI (Jurnal Pendidikan Khusus, 2018)
A learning result was a result obtained from someone?s learning effort and it could be enhanced through the usage of exact media. Because of the low learning result of class III students, especially mild mentally retardation children in SDN Gununganyar 273, the students needed exact media i.e. a cowrie shell modification in counting operation. A cowrie shell modification was a shell modified to count division operation which the form was simple and was made from the things around. The research purpose was to know whether the usage of cowrie shell modification media could enhance the learning result of counting operation to class III students or not, especially mild mentally retardation children numbering 30 children consisted of 26 regular children and 4 mild mentally retardation children. The research method used descriptive qualitative and quantitative. The data was obtained by the technique of observation, test, and interview. The techniques of observation and interview were used to obtain the qualitative data i.e. teacher?s activity and students? activity in learning. The test was used to obtain the quantitative data from the students? learning result of counting operation using cowrie shell modification media. The research result indicated that in the teacher?s activity in cycle I there were 7 points of good categories and 1 point unimplemented yet i.e. to guide the children during learning. In cycle II, all points of observation were implemented very well. In the students? activity in cycle I there was enhancement, from 8 points there was 1 very good point. In cycle II, there were 7 very good points and 1 good point. The interview result also indicated that in cycle I the children understood the material well but 1 child got difficulty in using the cowrie shell modification media. In cycle II, the children understood the material very well and there was 1 child got difficulty in using the cowrie shell modification media. The conclusion of this research was that the usage of cowrie shell modification media could enhance the learning result of counting to class III students in SDN Gununganyar 273, especially mild mentally retardation children. Keywords: cowrie shell modification, counting operation of division